Bitter ginger (Zingiber zerumbet) for patients with solid tumors with no treatment options: A pilot clinical study - Larissa Vieira de Queiroz; José Favoreto Neto; Fernando Luiz Affonso Fonseca; Carlos Cleomir Pinheiro; Auro del Giglio (Elsevier, 2024)
Introduction: Zerumbone is a natural compound found in bitter ginger plants (Zingiber zerumbet) that shows antiproliferative, antioxidant, anti-inflammatory, and analgesic properties. We aimed to investigate the role of zerumbone in improving the quality of life and symptom control in cancer patients with no treatment options. Methods: We conducted a pilot, non-randomized, single-center, open prospective, and systematic study on the use of 400 mg of zerumbone twice a day. Results: The study included 35 patients (mean age, 68 years; 64% men), of which 16 completed the eight-week study. The intention-to-treat population showed no significant changes in weight or sleep quality over the eight-week study. Assessments performed using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) showed significant improvements in the quality of life in the global (p = 0.072), activity (p = 0.0393), social (p = 0.0001), and emotional (p = 0.0023) dimensions. The Hospital Anxiety and Depression Scale (HADS) questionnaire scores showed significant improvement in anxiety (p = 0.032) and depression (p = 0.021), while the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) questionnaire scores also indicated a significant improvement (p = 0.001). Bitter ginger showed low toxicity. Conclusions: Bitter ginger showed promising results in improving the quality of life and reducing symptoms of anxiety and depression in the study population. A randomized placebo-controlled study is necessary to confirm these results.This trial was registered under the number FMABC: CAAE - 93459418.00000082, at ISRCTN (BIOMED CENTRAL) NUMBER 4388 (03/07/23) and at Plataforma Brasil (https://plataformabrasil.saude.gov.br/login.jsf)